Christie's House: The Benefits of Mining for Failures in the Nineteenth Century. Issue 1 (1st June 2022) - Dutt, Rajeshwari
Abstract : Using the example of an unbuilt house in San Juan del Norte on the Caribbean coast of Nicaragua in 1849, this essay argues for mining for instances of failures in the colonial archives to demonstrate the limits of imperial control in the nineteenth-century frontier and borderland regions of empire. Such studies can be a useful counterpoint to the narrative of imperial success and climax in the global nineteenth century.